Drosophila Dyrk2 plays a role in the development of the visual system. - Nathan Luebbering; Mark Charlton-Perkins; Mark Charlton-Perkins; Justin P Kumar; Pamela A Lochead; Stephanie M Rollmann; Tiffany Cook; Vaughn Cleghon (PLoS ONE, 2013)
The DYRKs (dual-specificity tyrosine phosphorylation-regulated kinases) are a conserved family of protein kinases that are associated with a number of neurological disorders, but whose biological targets are poorly understood. Drosophila encodes three Dyrks: minibrain/Dyrk1A, DmDyrk2, and DmDyrk3. Here we describe the creation and characterization of a DmDyrk2 null allele, DmDyrk2(1w17) . We provide evidence that the smell impaired allele smi35A(1) , is likely to encode DmDyrk2. We also demonstrate that DmDyrk2 is expressed late in the developing third antennal segment, an anatomical structure associated with smell. In addition, we find that DmDyrk2 is expressed in the morphogenetic furrow of the developing eye, that loss of DmDyrk2 in the eye produced a subtle but measurable defect, and that ectopic DmDyrk2 expression in the eye produced a strong rough eye phenotype characterized by increased secondary, tertiary and bristle interommatidial cells. This phenotype was dependent on DmDyrk2 kinase activity and was only manifest when expressed in post-mitotic non-neuronal progenitors. Together, these data indicate that DmDyrk2 is expressed in developing sensory systems, that it is required for the development of the visual system, and that the eye is a good model to identify DmDyrk2 targets.